2021
DOI: 10.1161/jaha.121.022060
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐Coated Balloon Versus Plain Balloon Angioplasty for Hemodialysis Dysfunction: A Meta‐Analysis of Randomized Controlled Trials

Abstract: Background Both drug‐coated balloon (DCB) angioplasty and conventional plain balloon angioplasty (PBA) can be implemented to treat hemodialysis dysfunction. The present study aims to compare the safety and efficacy of these 2 approaches by conducting a meta‐analysis of available randomized controlled trials. Methods and Results PubMed, Cochrane Library, and Embase databases were queried from establishment to January 2021. A total of 18 ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Four studies investigating the effect of DEB (21)(22)(23)(24) and nine studies investigating the effect of DCB were included in our NMA (12,(15)(16)(17)(18)(19)(20)(21)29). The results demonstrated that both DEB and DCB had a statistically higher patency rate compared with PBA at all time points, which was consistent with the results of several recently published studies (40,41). Meanwhile, both these studies demonstrated that the use of DCB did not cause a significant increase in patient mortality, indicating the high safety of DCB compared with PBA.…”
Section: Discussionsupporting
confidence: 86%
“…Four studies investigating the effect of DEB (21)(22)(23)(24) and nine studies investigating the effect of DCB were included in our NMA (12,(15)(16)(17)(18)(19)(20)(21)29). The results demonstrated that both DEB and DCB had a statistically higher patency rate compared with PBA at all time points, which was consistent with the results of several recently published studies (40,41). Meanwhile, both these studies demonstrated that the use of DCB did not cause a significant increase in patient mortality, indicating the high safety of DCB compared with PBA.…”
Section: Discussionsupporting
confidence: 86%
“…The treatment of PCB in both arms is to ensure all patients receive ethical standard of care treatment while testing the research hypothesis since PCB can now be considered standard of care, especially for AVF with recurrent stenosis. 20 TLPP and ACPP are chosen as the primary endpoints because the study is designed to treat all stenosis in the AVF circuit in addition to CAS. Furthermore, it is the ACPP that is clinically meaningful for the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Given the lack of clarity provided by the available RCTs, numerous systematic reviews and meta-analyses have been performed over the years. However, these have also been unable to provide a clearer sense of the effectiveness of DCB us in AV access, noting conflicting conclusions likely related to differences in the meta-analyses, including their unique inclusion criteria, availability of RCTs and other studies for inclusion based on time of publication, and different analytic methods (14,66,76,(103)(104)(105)(106)(107).…”
Section: Summary Of Studies and Meta-analysesmentioning
confidence: 99%
“…A 2021 meta-analysis by Fong et al included 12 RCTs and employed numerous types of analyses, with the majority suggesting a benefit associated with DCB use ( 105 ). Similarly, a 2021 meta-analysis by Liu et al included 18 RCTs and suggested DCBs improved TLPP and ACPP compared to POBA ( 106 ). However, this was followed by a 2022 meta-analysis by Luo et al including 14 RCTs which demonstrated no clear advantage of DCBs compared to POBA ( 73 ).…”
Section: Summary Of Studies and Meta-analysesmentioning
confidence: 99%